Intestinal microbiota mediates Enterotoxigenic Escherichia coli-induced diarrhea in piglets - Bin, Peng; Tang, Zhiyi; Liu, Shaojuan; Chen, Shuai; Xia, Yaoyao; Liu, Jiaqi; Wu, Hucong; Zhu, Guoqiang (BMC veterinary research, 2018)
Enterotoxigenic Escherichia coli (ETEC) causes diarrhea in humans, cows, and pigs. The gut microbiota underlies pathology of several infectious diseases yet the role of the gut microbiota in the pathogenesis of ETEC-induced diarrhea is unknown. By using an ETEC induced diarrheal model in piglet, we profiled the jejunal and fecal microbiota using metagenomics and 16S rRNA sequencing. A jejunal microbiota transplantation experiment was conducted to determine the role of the gut microbiota in ETEC-induced diarrhea. ETEC-induced diarrhea influenced the structure and function of gut microbiota. Diarrheal piglets had lower Bacteroidetes: Firmicutes ratio and microbiota diversity in the jejunum and feces, and lower percentage of Prevotella in the feces, but higher Lactococcus in the jejunum and higher Escherichia-Shigella in the feces. The transplantation of the jejunal microbiota from diarrheal piglets to uninfected piglets leaded to diarrhea after transplantation. Microbiota transplantation experiments also supported the notion that dysbiosis of gut microbiota is involved in the immune responses in ETEC-induced diarrhea. We conclude that ETEC infection influences the gut microbiota and the dysbiosis of gut microbiota after ETEC infection mediates the immune responses in ETEC infection.